The Midnight Library - Kohara, Kazuno (New York : Square Fish/Roaring Brook Press, 2022)
"Once there was a library that only opened at night. Step inside and meet the little librarian and her three assistant owls"--Provided by publisher.
Kirkus Starred
Publishers Weekly
School Library Journal
Booklist, June 2014
Horn Book, October 2014
Kirkus Starred, April 2014
Keywords: Animals -- Juvenile fiction; Books and reading -- Juvenile fiction; Libraries -- Juvenile fiction; Nocturnal animals -- Juvenile fiction; Animals -- Fiction; Books and reading -- Fiction; Libraries -- Fiction; Nocturnal animals -- Fiction; Animals -- Fiction; Books and reading -- Fiction; Libraries -- Fiction; Nocturnal animals -- Fiction; Picture books